Pemberdayaan masyarakat komoditi Bawang Merah dalam menghasilkan produk olahan unggulan Desa Polagan Kecamatan Galis Pamekasan - Moh. Amir Furqon; Wahyu Maulana; Niken Yudha Safitri (Riau Journal of Empowerment, 2022)
Horticultural commodities are potential commodities with high economic value and can continue to be developed and shallots are a source of livelihood for the agricultural community. The purpose of this PKM - PM is to provide solutions to maximize potential so that it becomes something of high economic value so as to improve a better standard of living. The partner is the “Sri Kuning” farmer group in the village of Polagan Galis Pamekasan. The PKM – PM method is community empowerment by providing assistance to produce processed products which are the village's superior products. The results of this PKM – PM include: 1. Creating processed products that become the village's superior products; 2. Understanding of digital marketing for marketing expansion; 3. Can determine a competitive selling price; and 4. Utilizing and maximizing the potential of the village so as to create zero waste of raw materials.